Glasgow Cathedral in the Thirteenth Century, from an Ancient Seal: With Sidelights on Contemporary History (Proceedings of the Society of Antiquaries of Scotland, 1918)
The art of seal-engraving was far advanced in Scotland in the thirteenth century. Among the early specimens of ecclesiastical seals those of Glasgow present features of great excellence, especially those executed during the episcopate of Robert Wishart (1272-1316). It is suggested that the representations of churches engraved on\r thirteenth-century seals are not conventional but real '” not necessarily accurate, however'” of the churches as they stood and that this applies not only to the churches and their style of architecture, but to the costumes of the clergy, the altar furniture, and the symbols depicted. The seal in question is the second chapter seal of Glasgow appended to a document circa 1280 A.D., that is, during the episcopate of Bishop Robert Wishart, who befriended Wallace and Bruce in the Great War of Scottish Independence. The extent to which the seal depicts actual details of the cathedral is considered.